Metabolomic analysis of methyl jasmonate treatment on phytocannabinoid production in Cannabis sativa - Welling, Matthew T.; Deseo, Myrna A.; O’Brien, Martin; Clifton, Jacob; Bacic, Antony; Doblin, Monika S. (Frontiers in Plant Science, 2023)
Cannabis sativa is a multi-use and chemically complex plant which is utilized for food, fiber, and medicine. Plants produce a class of psychoactive and medicinally important specialized metabolites referred to as phytocannabinoids (PCs). The phytohormone methyl jasmonate (MeJA) is a naturally occurring methyl ester of jasmonic acid and a product of oxylipin biosynthesis which initiates and regulates the biosynthesis of a broad range of specialized metabolites across a number of diverse plant lineages. While the effects of exogenous MeJA application on PC production has been reported, treatments have been constrained to a narrow molar range and to the targeted analysis of a small number of compounds. Using high-resolution mass spectrometry with data-dependent acquisition, we examined the global metabolomic effects of MeJA in C. sativa to explore oxylipin-mediated regulation of PC biosynthesis and accumulation. A dose–response relationship was observed, with an almost two-fold increase in PC content found in inflorescences of female clones treated with 15 mM MeJA compared to the control group. Comparison of the inflorescence metabolome across MeJA treatments coupled with targeted transcript analysis was used to elucidate key regulatory components contributing to PC production and metabolism more broadly. Revealing these biological signatures improves our understanding of the role of the oxylipin pathway in C. sativa and provides putative molecular targets for the metabolic engineering and optimization of chemical phenotype for medicinal and industrial end-uses.